The The Influence Of Profitability And Leverage On Tax Avoidance At PT Panin Sekuritas Tbk For The Period 2017 - 2023 - Harahap, Shela Nopyanti; Marliza, Yayuk; Oktavianie, Rian (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
This study aims to determine the effect of Profitability and Leverage on Tax Avoidance at PT Panin Sekuritas Tbk for the 2017-2023 period. This study is a quantitative study. The operational variables of this study are profitability and leverage as independent variables and tax avoidance as the dependent variable. The data used in this study are secondary data with documentation data collection methods. Data analysis used in this study is multiple linear regression analysis. The final results of this study are: First, profitability (X1) does not have a significant effect on tax avoidance with a value of -2.77645 < -0.580 < 2.77645, Second leverage (X2) does not have a significant effect on tax avoidance with a value of -2.77645 < -0.586 < 2.77645. Meanwhile, based on the results of the F test, it shows that simultaneously profitability and leverage do not have a significant effect on tax avoidance with a value of 0.200 < 7.709. Where 9.1% is influenced by profitability and leverage, and 90.9% is influenced by other factors.